CAV1-CAVIN1-LC3B-mediated autophagy regulates high glucose-stimulated LDL transcytosis. Issue 6 (2nd June 2020) - Bai, Xiangli; Yang, Xiaoyan; Jia, Xiong; Rong, Yueguang; Chen, Lulu; Zeng, Tianshu; Deng, Xiuling; Li, Wenjing; Wu, Guangjie; Wang, Ling; Li, Ye; Zhang, Jing; et al.
ABSTRACT: Diabetes is a recognized high-risk factor for the development of atherosclerosis, in which macroautophagy/autophagy is emerging to play essential roles. The retention of low-density lipoprotein (LDL) particles in subendothelial space following transcytosis across the endothelium is the initial step of atherosclerosis. Here, we identified that high glucose could promote atherosclerosis by stimulating transcytosis of LDL. By inhibiting AMPK-MTOR-PIK3C3 pathway, high glucose suppresses the CAV-CAVIN-LC3B-mediated autophagic degradation of CAV1; therefore, more CAV1 is accumulated in the cytosol and utilized to form more caveolae in the cell membrane and facilitates the LDL transcytosis across endothelial cells. For a proof of concept, higher levels of lipids were accumulated in the subendothelial space of umbilical venous walls from pregnant women with gestational diabetes mellitus (GDM), compared to those of pregnant women without GDM. Our results reveal that high glucose stimulates LDL transcytosis by a novel CAV1-CAVIN1-LC3B signaling-mediated autophagic degradation pathway. Abbreviations: 3-MA: 3-methyladenine; ACTB: actin beta; AMPK: AMP-activated protein kinase; Bafi: bafilomycin A1 ; CAV1: caveolin-1; CAVIN1: caveolae associated protein 1; CSD: the CAV1 scaffolding domain; GDM: gestational diabetes mellitus; IMD: intramembrane domain; LIR: LC3-interacting region; MAP1LC3/LC3: microtubule- associated protein 1 light chain 3; MFI: mean fluorescence intensity; MTOR: mechanistic target of rapamycin kinase; PIK3C3/VPS34: phosphatidylinositol 3-kinase catalytic subunit type 3; SQSTM1/p62: sequestosome 1.